TINJAUAN YURIDIS PENYELESAIAN SENGKETA TANAH WARIS ETNIS LAPORO MENURUT HUKUM ADAT BUTON: STUDI PADA KELURAHAN KARYA BARU KECAMATAN SORAWOLIO KOTA BAUBAU - Rachmat Taibu; Nurfadhilah Rahma (Jurnal Ilmu Hukum Kanturuna Wolio, 2026)
This research examines the resolution of land inheritance disputes within the Laporo ethnic community in Karya Baru Sub-District, Sorawolio District, Baubau City, based on Butonese customary law. The study is motivated by frequent conflicts among heirs regarding the distribution of inherited land, despite the formal recognition of customary inheritance law within Indonesia's legal system. The research aims to analyze the process of dispute resolution under customary law and to identify the obstacles encountered in its implementation. Using an empirical juridical approach, data were collected through interviews and observations involving local customary leaders and community members. The findings show that inheritance disputes are initially resolved through family deliberation. If no agreement is reached, the matter is escalated to customary authorities, who mediate based on traditional norms, justice, and consensus. However, challenges such as unilateral land control, lack of written evidence, unequal land division, and poor communication among heirs often hinder effective resolution. Although customary decisions do not have formal legal binding force, they are respected by the community as legitimate outcomes rooted in local wisdom and cultural values.